2001
DOI: 10.1038/35066075
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome territories, nuclear architecture and gene regulation in mammalian cells

Abstract: The expression of genes is regulated at many levels. Perhaps the area in which least is known is how nuclear organization influences gene expression. Studies of higher-order chromatin arrangements and their dynamic interactions with other nuclear components have been boosted by recent technical advances. The emerging view is that chromosomes are compartmentalized into discrete territories. The location of a gene within a chromosome territory seems to influence its access to the machinery responsible for specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

76
1,609
0
18

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,114 publications
(1,703 citation statements)
references
References 111 publications
76
1,609
0
18
Order By: Relevance
“…Numerous recent studies have also shown that nuclear architecture, higher order chromatin organization and the topology of chromosomal territories in interphase cells might be involved in gene regulation. 22 A comprehensive model for these interactions does not yet exist but as this study shows, nuclear chromatin phenotype provides very specific clues to the underlying pathology and its study is likely to be extremely important in cancer pathobiology.…”
Section: Discussionmentioning
confidence: 90%
“…Numerous recent studies have also shown that nuclear architecture, higher order chromatin organization and the topology of chromosomal territories in interphase cells might be involved in gene regulation. 22 A comprehensive model for these interactions does not yet exist but as this study shows, nuclear chromatin phenotype provides very specific clues to the underlying pathology and its study is likely to be extremely important in cancer pathobiology.…”
Section: Discussionmentioning
confidence: 90%
“…Theodore Boveri (1862Boveri ( -1915 was the first researcher who linked nuclear organization and genome stability. Studying Ascaris and sea urchin eggs, he described for the first time 'chromosomal regions' ('chromosome territories' [Cremer and Cremer, 2001]). Chromosomal regions are regions within the 3D nuclear space in which chromosomes tend to be found in normal cells.…”
Section: Boveri's Legacy: In Search Of the Mechanisms That Regulate Amentioning
confidence: 99%
“…Chromosomal DNA in the cell nucleus is distributed according to its nucleotide composition (guanine + cytosine content, or GC level), the GC-poorest DNA being located more peripherally with respect to the GC-richest DNA (Sadoni et al 1999;Cremer and Cremer 2001;Saccone et al 2002). This type of DNA distribution defines two nuclear compartments having different GC levels as well as different structural and functional properties (see Bernardi 2004 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies demonstrated that in spherically shaped nuclei (such as those of lymphocytes), the radial positioning of human chromosome territories is generally in accordance with their gene density (Cremer and Cremer 2001;Boyle et al 2001). This type of nuclear chromosome distribution was first shown for the human chromosomes 18 and 19, which are located in different radial positions, namely at the periphery and in the interior of the nucleus, respectively (Croft et al 1999).…”
Section: Introductionmentioning
confidence: 99%